Scoring first relevance in knockout promotion to spanish LaLiga smartbank - Marcos Olvera-Rojas, Pedro Femia-Marzo, Alfonso Castillo-Rodríguez (Journal of Human Sport & Exercise, 2023)
The aim of the present study was to examine the effect´s relevance of scoring first in knockout promotion to the Spanish Liga Smartbank and succeeding´s probability in the knockout round according to contextual parameters. The sample consisted in all knockout rounds not ending scoreless (n = 199) played in the knockout promotion to Spanish Liga Smartbank between 2004/2005 to 2018/2019 season. Data were examined by descriptive analysis, chi-square tests and binary logistic regressions. Results shown statistically significant values when scoring first and moving through to the next qualifying round (?² [1 df] = 32.37; p < .001). Teams opening knockout round as a home team and scoring first, move through to the next round 61.7% of times while teams opening knockout round as an away team and scoring first, move through to the next round 79.4% of the times (Total OR = 6.19). Moreover, significant results were found relative to the importance of gaining advantage in first-leg match and scoring first in the second-leg match. This information could be useful for coaches and performance analysts, being applicable to competition in order to prevent the opposite team from scoring a goal and to find tactical options that allow your team getting ahead on the scoreboard.